Case report: Successful laparoscopic management of early abdominal pregnancy - Li, Haixia; Feng, Limin; Zhang, Shengpeng (Frontiers in Medicine, 2025)
BackgroundAbdominal pregnancy is characterized by the implantation of the gestational sac within the peritoneal cavity, specifically outside the fallopian tubes, ovaries, and cervix. This exceedingly rare form of ectopic pregnancy accounts for about 1% of all ectopic pregnancies. When rupture occurs, it can result in a life-threatening situation for the patient, necessitating immediate medical intervention.Case informationIn this study, we report a 33-year-old female patient who presented with abdominal pain and was subsequently diagnosed with an early abdominal pregnancy. Laparoscopic intervention revealed gestational tissue and a rupture site located in the pouch of Douglas. The gestational tissue was successfully excised via laparoscopy, and the rupture site was sutured to achieve hemostasis. Postoperative histopathological analysis confirmed the presence of chorionic villi and trophoblast cells.ConclusionThis case highlights the critical importance of precise diagnosis and laparoscopic intervention in the management of abdominal pregnancy. It is imperative for clinicians to exercise a prudent approach in the diagnosis and treatment of abdominal pregnancy, utilizing a comprehensive assessment that integrates medical history, clinical manifestations, and auxiliary diagnostic tests to enhance the detection and comprehension of this condition.